2014
DOI: 10.1002/pc.23177
|View full text |Cite
|
Sign up to set email alerts
|

Bending actuation and charge distribution behavior of polyurethane/carbon nanotube electroactive nanocomposites

Abstract: The electroactive nanocomposite films were fabricated using polyurethane (PU) with modified carbon nanotubes (CNTs) as the filler. The CNTs were modified using microwave‐induced polymerization route and they were found to be highly dispersed in polar solvents such as dimethylformamide. The modified CNTs were characterized using transmission electron microscopy, field emission scanning electron microscopy, thermogravimetric analysis, and X‐ray photoelectron spectroscopy. To evaluate these films we mainly focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…14 Hence, S z can be improved at the same electrical field by enhancing electromechanical sensitivity (β, β = ε r /Y) through increasing ε r and decreasing Y of elastomer. To increase ε r , many fillers, including carbon nanotubes, 15,16 carbon nanospheres, 12 graphene nanosheets, 17,18 and organic strong polar azobenzene 19 have been chemically/physically incorporated into TPU to form the dielectric elastomer composites. However, only limited actuation strain was observed in such TPU composites due to their further increased Y.…”
Section: Introductionmentioning
confidence: 99%
“…14 Hence, S z can be improved at the same electrical field by enhancing electromechanical sensitivity (β, β = ε r /Y) through increasing ε r and decreasing Y of elastomer. To increase ε r , many fillers, including carbon nanotubes, 15,16 carbon nanospheres, 12 graphene nanosheets, 17,18 and organic strong polar azobenzene 19 have been chemically/physically incorporated into TPU to form the dielectric elastomer composites. However, only limited actuation strain was observed in such TPU composites due to their further increased Y.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organoclay lead to the cell size reduction, however, uneven dispersion of the organoclay in the polyol solution was observed. While the incorporation of carbon nanotubes or graphenes in PUF has shown to improve its thermal, electrical, and mechanical properties [4,9,[22][23][24][25], studies on their influence on acoustic damping properties are limited [13,14,26]. A few studies reported the acoustic damping properties of PUF without correlation to its airflow resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, two mechanisms of electric field induced bending deformation have been suggested, which are migration of ionized solvents (plasticizers) induced thinner solvent enrichment layer (S-R layer) [21,22,24] and asymmetric distribution of space charges (i.e. bending electrostriction effect) [35,36]. Since the plasticizers are absence in the PUUs, the mechanism of S-R layer is not suitable to explain the bending deformation.…”
Section: Bending Actuation Mechanism Of Puusmentioning
confidence: 99%